Copper-based hydrogels with dicarboxylate spacer ligands for selective carbon dioxide separation applications. (17th October 2018) - Al-Dossary, Mona; Padhy, Harihara; Xu, Feng; Behzad, Ali R.; el Tall, Omar; Rothenberger, Alexander
Abstract : Dicarboxylate spacer ligands enhanced the rigidity, porosity, surface area, and CO2 /N2 and CO2 /CH4 selectivity of Cu 2+ -based poly(methyl vinyl ether- alt -maleic anhydride) hydrogels. Abstract : In this study, we report a simple method for synthesizing copper-containing polymer hydrogels made from nontoxic poly(methyl vinyl ether- alt -maleic anhydride) (PVM-MA) in the absence or presence of added carboxylate ligands: dicarboxylates, such as adipate and terephthalate or tricarboxylates, such as nitrilotriacetate (NTA) and trisodium citrate. Our copper hydrogels are wet precursors to a new family of amorphous porous materials, consisting of a metal–polycarboxylate backbone and carboxylate spacer ligands between polymer strands engineered via non-covalent interactions. Rheological measurements revealed that the mechanical stability of the hydrogels was enhanced by the addition of supplementary dicarboxylate ligands. We determined that the optimal ratio of polymer to dicarboxylate to Cu 2+ was 10 : 4 : 2.5. Our scanning electron microscope (SEM) and cryo-SEM imaging and physical adsorption measurements revealed the formation of pores. The Brunauer–Emmett–Teller (BET) surface area of the dried hydrogels was tunable due to the addition of supplementary dicarboxylate ligands. The BET surface area increased from 177.96 m 2 g −1 in a dried hydrogel without added dicarboxylate to 646.9 and 536.4 m 2 g −1 by the addition of adipate and terephthalate, respectively. Moreover, addition of dicarboxylate ligands increased the pore volume and CO2 gas adsorption capacity. Separation of CO2 from post-combustion flue gases is important for environmental and economic sustainability. Our copper-based hydrogel with dicarboxylate spacer ligands offers the possibility of a new material for post-combustion CO2 capture.